Increasing Area of Green Mussel Culture in Ao Sriracha, Chon-Buri Province - Monton Anongponyoskun,; Shettapong Meksumpun, (Agriculture and Natural Resources, 2007)
Nowadays, in Ao Sriracha, Chon-Buri province, fishermen install sea floating rafts of green mussel in extensive area. The RADARSAT imaged data in the years 2001 to 2004 showed that floating rafts of green mussel increased 3 times from 0.5 km2 to 1.5 km2. Increasing area of green mussel culture enlarged in the northern and the middle parts of Ao Sriracha, but in the southern part, the floating rafts were intensive. POM 2 D (Princeton Ocean Model 2 dimensions) based on momentum balance, mass balance under conditions of well mixed seawater and no effects of wind was simulated. Assuming that seawater current in Ao Sriracha was only affected by tide, seawater height at the southern part was transferred to be boundary condition in the model. Results of the model showed that averaged velocity of seawater flowing pass the area of green mussel culture from north to south was about 0.2-0.3 m/sec in June and from south to north was about 0.3-0.4 m/sec in September. Patterns of averaged circulation related to increasing area of floating rafts for supporting spat of green mussel from the northern part. For suitable management of the culture area, the floating rafts should be arranged to leave wide space between them which was large enough for good circulation of seawater and dispersion of green mussel spats. If there was good distribution of spats, the area of southern part could be extended for floating rafts to raise marine farms and marine products. At the same time, it would be the ways to keep good environments for sustainable marine cultures.